2018
DOI: 10.1289/ehp2732
|View full text |Cite
|
Sign up to set email alerts
|

A National Multicity Analysis of the Causal Effect of Local Pollution, NO2, and PM2.5 on Mortality

Abstract: Causal-modeling techniques, each subject to different assumptions, demonstrated causal effects of locally generated pollutants on daily deaths with effects at concentrations below the current EPA daily [Formula: see text] standard. https://doi.org/10.1289/EHP2732.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…The general magnitude of our results aligns with previous studies [19,20], but there is inconsistency among results that have been reported thus far between various studies and even within the same study using different causal methods. Using IV analysis, Schwartz et al found a 1.54% increase in daily deaths per 10 μg/m 3 PM 2.5 increase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The general magnitude of our results aligns with previous studies [19,20], but there is inconsistency among results that have been reported thus far between various studies and even within the same study using different causal methods. Using IV analysis, Schwartz et al found a 1.54% increase in daily deaths per 10 μg/m 3 PM 2.5 increase.…”
Section: Discussionsupporting
confidence: 91%
“…Using IV analysis, Schwartz et al found a 1.54% increase in daily deaths per 10 μg/m 3 PM 2.5 increase. In contrast, they reported that the marginal structural model estimate for PM 2.5 was 0.75% for the same increment [19]. In another study by Schwartz et al 2015, a 0.5% daily mortality increase was reported to be a result of a 1 μg/m 3 PM 2.5 increase using IV and propensity score methods [20].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, while effects of NO 2 appear to be confounded by co-pollutants, there is still evidence of an association after accounting for this. In a recent causalmodelling analysis of NO 2 , PM 2.5 and mortality in 135 US cities, Schwartz et al concluded that NO 2 was independently associated with mortality, although residual confounding by other pollutants could not be ruled out [7]. Similarly, in their systematic review and metaanalysis attempting to distinguish effects of particulate matter and NO 2 on mortality and hospital admissions in time-series studies, Mills et al concluded that effects of NO 2 were generally robust to inclusion of particulate In the absence of publication bias, points should be symmetrically distributed around the vertical line, with smaller studies (larger standard errors on vertical axis) more widely scattered.…”
Section: Overall Rating Of Quality and Strength Of Evidencementioning
confidence: 99%
“…A particular complicating factor is whether NO 2 itself is to blame, or whether it is simply acting as a marker for specific air pollution sources i.e. emissions from vehicles [6,7]. Carbon monoxide and certain chemical components of fine particulate matter, also primarily originating from vehicle emissions, are key potential confounders, given their well-established pathophysiological mechanisms of action on cardiac ischemia [8].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of exposure assessment, 15 studies used PM 2.5 estimated from spatio-temporal prediction models [2••, 3, 7, 8, 17, 18, 21, 22••, 23-25, 27-30], two [13,14] used the EPA Downscaler (DS) model [31], five used PM 2.5 concentrations measured at monitoring stations and downloaded from EPA's Air Quality System (AQS) database or other county monitors [10,15,16,19,26], two used measurements from the Harvard Supersite in Boston [12,20], and two studies compared results obtained using five [11] and ten [9] different exposure models. In terms of exposure duration, 15 studies examined mean annual PM 2.5 , ten studies daily PM 2.5 , and one study included both daily and annual averaged exposures.…”
Section: Summary Of Findingsmentioning
confidence: 99%